Fgf-18 is required for osteogenesis but not angiogenesis during long bone repair - Behr, Björn; Sorkin, Michael; Manu, Alina; Lehnhardt, Marcus; Longaker, Michael T.; Quarto, Natalina (Tissue engineering, 2011)
Bone regeneration is a complex event that requires the interaction of numerous growth factors. Fibroblast growth factor (Fgf)-ligands have been previously described for their importance in osteogenesis during development. In the current study, we investigated the role of Fgf-18 during bone regeneration. By utilizing a unicortical tibial defect model, we revealed that mice haploinsufficient for Fgf-18 have a markedly reduced healing capacity as compared with wild-type mice. Reduced levels of Runx2 and Osteocalcin but not Vegfa accompanied the impaired bone regeneration. Interestingly, our data indicated that upon injury angiogenesis was not impaired in Fgf-18+/− mice. Moreover, other Fgf-ligands and Bmp-2 could not compensate for the loss of Fgf-18. Finally, application of FGF-18 protein was able to rescue the impaired healing in Fgf-18+/− mice. Thus, we identified Fgf-18 as an important mediator of bone regeneration, which is required during later stages of bone regeneration. This study provides hints on how to engineering efficiently programmed bony tissue for long bone repair.